Wpływ globalizacji rynku IT na procesy zarządzania i wytwarzania systemów informatycznych - Frączkowski, Kazimierz (The Influence of the IT Global Market on the Management and Production Processes of Computer Systems, 2005)
This paper analyzes factors that have direct influence on new computer systems such as technologies and tools of productions, as well as management methods of executing teams. The main focus is set upon exterior factors that are connected with the access to IT (Informatic Technology), internet service market, competition between companies that forces them to decrease the costs and shorten the time of production, and to increase quality. The changes resulting from the activity of corporations and EU directives concerning such programs as eGovernment, eHealth, eLearning and others, influence the needs and the kind of support for social and economic activities through IT. The global access and the usage of services supported by informatic solutions increase also many negative phenomena such as globalization of electronic crime including hacking, virus terrorism and others.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 269-277